In Vivo Identification of the Iron-Chelating Potential of Kwini Mango (Mangifera odorata Griff) Leaf Extract in Iron Overload Cases - Titi Pudji Rahayu; Sapto Yuliani; Hari Susanti; Sugeng Supriyanto; Septiana Indratmoko (Jurnal Penelitian Pendidikan IPA, 2025)
Iron overload (IO) is a condition characterized by an abnormal accumulation of iron in the body, which affects vital organs such as the liver, heart, pancreas, and endocrine tissues. Kwini mango (Mangifera odorata Griff) leaves, which contain mangiferin (a phenolic compound), have the ability to chelate Fe3+ by promoting the oxidation of Fe2+, potentially lowering blood iron levels. This study aimed to explore the potential of kwini mango leaf extract (KMLE) as an in vivo iron chelator for treating IO, using blood samples from an IO patient. The in vivo study assessed the effects of KMLE on ferritin, SGPT, SGOT, BUN, creatinine, and serum hematology levels in blood samples. Additionally, liver and kidney histopathology were examined as markers of iron chelation. The extract's standardization was performed to determine the mangiferin content in KMLE. The in vivo results showed a decrease in ferritin, SGPT, SGOT, BUN, creatinine, and hematological parameters. Comparisons between the KMLE group, deferoxamine group, and mangiferin group indicated a significant reduction in ferritin levels in both the deferoxamine and mangiferin groups when compared to the KMLE group at doses of 50 mg/200 g BW and 100 mg/200 g BW (Asym. Sig. (2-tailed) < 0.05). A similar pattern was observed for reductions in SGPT, SGOT, BUN, and creatinine levels at the same doses (Asym. Sig. (2-tailed) < 0.05). No significant difference was observed in the KMLE group at a dose of 200 mg/200 g BW (Asym. Sig. (2-tailed) > 0.05). KMLE demonstrates the potential to reduce serum ferritin, SGOT, SGPT, BUN, creatinine, and improve liver histopathology, suggesting its effectiveness as an iron chelator for treating IO.